Australian women’s experiences of post-partum rectus diastasis: A qualitative study - Siobhan Elizabeth Fitzpatrick; Kristen Foley; Tamara Crittenden; David Watson; Nicola R Dean (Women's Health, 2024)
Background: Post-partum rectus diastasis, or the separation of the abdominal muscles after pregnancy, occurs in conjunction with physical symptoms and impaired quality of life. In Australia, health funding for surgery to treat diastasis was ceased in 2016, but reinstated in mid-2022, providing a unique context from which women’s experiences of this condition can be analysed. Objectives: The objective is to examine the experiences of Australian women with post-partum rectus diastasis. Design: This is an interview-style study with qualitative content analysis. Methods: Women diagnosed with rectus diastasis were recruited to complete a baseline questionnaire (n = 45). Twenty-three responded to invitation for one-on-one interview via Zoom® between November 2021 and May 2022. Interviews were recorded, transcribed, and analysed using qualitative content analysis to identify key themes. Results: Eighteen women had undergone caesarean section and eight had twins. Thirteen had private health insurance. Women were most often diagnosed by a physiotherapist (n = 10). Key themes identified included changed physical appearance and function; issues with self-esteem and intimacy; barriers to treatment; lack of recognition as a medical condition; and overall frustration. The impact of rectus diastasis extended beyond physical and psychological symptoms to affect women’s social functioning, child rearing, and return to work. There was a complex interaction between healthcare providers’ knowledge of rectus the removal of funding for surgical treatment, and limitations of conservative therapy, with women’s lived experiences and symptoms. The lack of an established medical definition also influenced the experiences of these women and their engagement with treatment. Conclusion: This study contextualizes women’s experience of post-partum rectus diastasis with respect to the unique landscape of Australia’s healthcare economy and provides evidence of women’s absorption of health policy surrounding this condition. Our qualitative analysis provides critical knowledge for future quantitative studies, the results of which in combination could advance the definition of rectus diastasis and inform healthcare policy surrounding treatment.